The So-Called London Baptist Education Society of 1752 – Some Further Explorations. (3rd July 2019) - Clarke, Anthony
ABSTRACT: This article explores the first attempt by Particular Baptists in London to fund and organise education for ministers, through the establishment in 1752 of what has often been called the London Baptist Education Society. It considers the background to the Society, the way the Society sought to work and contested questions like its actual name. It then explores how the ending of this Society might have been connected with the establishment of a new Education Society in 1804 and then Stepney Academy (now Regent's Park College) in 1810. It argues that while a financial continuation between the Society of 1752 and Stepney Academy is not certain, there are clear connections in people and purpose. The article is followed by a transcript of the minutes of the Education Society, making them publicly available for the first time.